Ecological - hygienic aspects and safety parameters of the use of the Zaragen insecticide in agriculture - H.O. Kosimov; H.J. Salomova (Universitas Muhammadiyah Sidoarjo, 2019)
This article states major results of multifaceted, comprehensive hygienic and toxicological studies, Zaragen can be recommended for use in agriculture on cotton, tomato and potato crops as an insecticide with mandatory compliance with the recommended consumption rates, hygienic standards and regulations, safety rules for the use of pesticidal preparations.